Jurnal Abdimas Hukum Adat Batak Karo Dan Yurisprudensi Dalam Hak Mewaris - Tarigan, Edi Kristianta; Darmayanti, Erni; Amaniarsih, Dwi Suci; Simatupang, Boby Daniel; Ginting, Erwin; Khadafi, Muhammad (LPPM Universitas Potensi Utama, 2024)
Customs are an order of life in Karo society, for example marriage, death which gives birth to heir rights. In Karo society, legal plurality is an indisputable reality. Karo custom places men and women in unequal/unequal positions. Boys as successors to the clan have a higher (superior) position and receive honors in various traditional events, both at weddings and mourning (death) events as well as other traditional events, including in the distribution process. inheritance. In Karo society, inheritance of inheritance is given to daughters only because of the generosity of their brothers, therefore property received by daughters is called pemerean or a sign of affection or appreciation. According to the Karo tradition, daughters are considered to have no rights to their parents' families because they have become part of their husband's family. The patrilineal-based Karo customary inheritance law has begun to shift towards bilateral-based inheritance law, this is also supported by the Supreme Court of the Republic of Indonesia with many judge decisions being used as jurisprudence for judges in deciding inheritance cases for Batak customs, especially the Karo Batak custom, that girls have the same rights as boys. Then, to strengthen this regulation, the Supreme Court issued Perma No. 2 of 1972 for Judges throughout Indonesia to follow existing jurisprudence to decide the same case.